Tingkat Penggunaan ChatGPT dalam Pembelajaran di Era Digital pada Mahasiswa PGSD - Jaya, I Ketut Manik Asta; Suastini, Ni Nyoman (Jurnal PGSD, 2025)
This research aims to examine the level of ChatGPT application usage among university students in digital learning era. This study adopts a quantitative research method, utilizing a questionnaire distributed through Google Forms. The questionnaire consists of closed-ended questions using a Likert sccale with 4 options: Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD). The questionnaire comprises 6 indicators, elaborated into 30 statement items. The results of the Validity Test show that the overall calculated r value is greater than the r-table value, at a significance level of 5%. The Reliability Test results indicate that the coefficient alpha reliability (Cronbach Alpha) in each indicator is greater than 0.5, indicating that the research instrument is reliable. This study involved 60 respondents, who are students from the Department of Primary School Teacher Education, Faculty of Dharma Acarya, State Hindu University of I Gussti Bagus Sugriwa Denpasar. The research findings show the average percentage across all indicators, revealing that 25.33% of respondents strongly agree, while 45% agree with the use of ChatGPT in lectures. Additionally, an average of 27.83% of respondents disagree with the use of ChatGPT in lectures, and 1.83% strongly disagree. It can be concluded that 70.33% of respondents support the implementation of ChatGPT in the learning process in the digital era.